Isolation of Tracheopasmolytic Compounds From Piper cubeba Fruits - Wahyono .; L. Hakim; S. Wahyuono; A. Mursyidi; R. Verpoorte; H. Timmerman (Indonesian Journal of Pharmacy, 2003)
The fruits of Piper cubeba (kemukus;Javanese)have been used in traditional medicine to treat illnesses such as asthma. Extracts were prepared by gradual maceration of the dried fruits with n-hexane, and by extraction of the residue with ethanol, and were tested for their tracheospasmolytic effects on isolated guinea-pig trachea contracted with metacholine at a dose of 0.25 mg/ml. Both extracts demonstrated spasm inhibition but the effect of the ethanol extract was lower than that of the n-hexane extract. However, TLC analysis did not distinguish between the extracts. The ethanol extract was then partitioned with n-hexane, and the first and second n-hexane extracts were combined and dried before further fractionation using vacuum liquid chromatography. The fractions were tested for tracheospasmolytic effects. Two active fractions were obtained and separated by column chromatography and preparative TLC. Four pure compounds were obtained. One of these is a lignan compound and identified as dihydrocubebin, had tracheospasmolytic activities.Key words: Piper cubeba; lignan, dihydrocubebin; tracheospasmolytic effect.